Redefining religious authority: how Dato' Seri Dr. Haji Zulkifli Mohamad Al-Bakri uses X (formerly Twitter) to share Islamic insights and engage with modern issues - Shah Jahan, Shah Nur Anniesa; A. Rashid, Siti Maisarah; Zamri, Nurin Alya; Razali, Khairil Azwar (Kulliyyah of Sustainable Tourism and Contemporary Languages (KSTCL), 2025)
This research is categorized under communication studies, which employ the interconnection between religion and media. X (formerly Twitter) has been chosen as it promotes the elements of engagement far beyond the other social media applications; more specifically, the use of X by Malaysian religious figures now prioritizes this platform to engage with the audience. Dato’ Seri Haji Zulkifli was chosen as his account is remarkable among other muftis, with the highest followers on X, demonstrating his noticeable influence on that platform. This article aims to investigate the patterns of engagement used by Dato’ Seri Haji Zulkifli and analyze how the patterns contribute to facilitating the discourse. Using a mixed-method approach, 215 tweets between January 2023 and March 2024 were examined using basic descriptive statistics and thematic content coding. According to the results, posts classified as "direct answer/clarification" received the most interaction and visibility, but posts classified as "promotional" or "casual content" received less engagement. These findings suggest that preserving digital religious authority and effectively interacting with audiences on digital platforms relied heavily on clarity, relevance, and an authoritative tone.